Pengaruh Disiplin dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Yuan Wira Perdana - Dewi Jayanti Nazara; Lingga Yuliana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to identify discipline and motivation on employee performance. This study is a qualitative descriptive study. Respondents are employees of PT. Yuan Wira Perdana. The data source uses primary data. Primary data was obtained from interviews with employees of PT Yuan Wira Perdana which were conducted in November 2024. The results of the study indicate that there is an influence between discipline and motivation on employee performance at PT Yuan Wira Perdana. The managerial implications in this study are that companies must be adaptive in responding to matters related to discipline and motivation. The need for a draft of regulations that can provide achievements and sanctions for violators of discipline and the need for stimulus so that employees can be motivated to work such as employee gathering activities, providing incentives, certified training can be some options for this.